Konkurencyjność produkcji wieprzowiny w Polsce na tle największych producentów na świecie - Szymańska, Elżbieta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The aim of the research was describing the competition position of pork producers in Poland. The research was connected with the level of cost in comparison with the biggest producers of this sort of meat. In the research the information form LEI report form Wageningen was used. The analysis includes pig farms in Brazil, Canada, the USA, China, Holland, and Poland. The research shows that Poland has a significant share in pork production in the world, but has little importance in the world export. The costs of production are lower in Brazil, Canada and in the USA. In Poland, the highest cost of production is influenced by existence of small farms, high prices of industrial fodder, laborious technology of raising and low level of investment. To increase export, the pork producers should take action to make large batch of homogeneous goods with high quality and competitive price. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 656-667